Reflections on global law - Musa, Shavana; Volder, Eefje de (BRILL, 2013)
Reflections on Global Law provides an interesting and vital look into the newly emerging field of global law. It allows the possibility for readers to discover global law from the perspective of various academic experts who stem from a whole range of different legal disciplines.